Pengaruh Tingkat Pendapatan, Literasi Keuangan dan Suku Bunga Terhadap Minat Menabung Pada Koperasi Dana Karya SariDesa Adat Bugbug - Ni Wayan Sri Widari; Dewi, Luh Gede Kusuma (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effect of income levels, financial literacy and interest rates on interest in saving in the work of the traditional bugbug village fund cooperative. The type of research used is a causal quantitative type. This study uses primary data obtained by distributing questionnaires or questionnaires. The collection of samples by purposive sampling technique and obtained 100 samples. The analytical method used is descriptive statistical analysis, classical assumption test, multiple linear regression test, and hypothesis testing with the help of SPSS 26.0 for windows application. The results of this study indicate that (1) the level of income, financial literacy and interest rates have a positive effect on interest in saving in the work of the traditional bugbug village fund cooperative. Keywords : Income level, Financial Literature, and Interest Rates